Coagulation, anticoagulation and pancreatic carcinoma - Nakchbandi, Inaam; Löhr, J.-Matthias (Nature Clinical Practice. Gastroenterology & Hepatology, 2008)
An increase in coagulation in patients with pancreatic carcinoma has long been documented. In this Review, we present what is known about the pathophysiology of increased coagulation in cancer and how it applies to pancreatic carcinoma. The relationship between the activation of coagulation or symptomatic thromboembolic disease and the development of pancreatic carcinoma is explored. Data on the relationship between thromboembolic disease and the behavior of pancreatic cancer before, during or after a diagnosis is made are also reviewed. Finally, the rationale and evidence for the use of oral anticoagulants or heparin in patients with pancreatic carcinoma is presented. This Review is a critical appraisal of what is known, and when the evidence is acceptable, on the subject of thromboembolism, anticoagulation, and treatment with anticoagulants in patients with pancreatic carcinoma.
Gesehen am 28.06.2021